Betulin terpenoid targets OVCAR-3 human ovarian carcinoma cells by inducing mitochondrial mediated apoptosis, G2/M phase cell cycle arrest, inhibition of cell migration and invasion and modulating mTOR/PI3K/AKT signalling pathway - Yang, Qin; Fei, Zhiyi; Huang, Chunyan (Cellular and Molecular Biology, 2021)
The main purpose of the current research work was to study in vitro anticancer effects of betulin in OVCAR-3 human ovarian carcinoma cells along with examining its effects on cellular apoptosis, cell cycle phase distribution, cell migration and invasion and mTOR/PI3K/AKT signalling pathway. The cell proliferation of OVCAR-3 cells at various doses of the drug was studied by CCK8 cell viability assay. Effects on cell apoptosis were studied by fluorescence microscopy and western blot. Effects on cell cycle were evaluated by flow cytometry and western blot. Transwell assays were used to study effects on cell migration and invasion. The results indicated that betulin led to significant reduction of OVCAR-3 cell viability in a dose-dependent as well as time dependent manner. Betulin also led to reduction in cell colonies. The anticancer effects of betulin were due to the induction of apoptosis which was seen by increased apoptotic cells with yellow and orange fluorescence. Betulin prompted mitochondrial apoptosis which was also associated with alteration in the apoptosis-related protein expression (Bax, Bad and Bcl-2 and Bcl-xL). The molecule also led to G2/M phase cell cycle arrest on OVACR-3 ovarian carcinoma cells. It was also observed that betulin could inhibit the migration and invasion of the ovarian cancer cells in a concentration-dependent manner. Betulin molecule also resulted in blocking of mTOR/PI3K/AKT signalling pathway. In conclusion, this study clearly indicates the anticancer effects of betulin natural product in OVCAR-3 human ovarian cancer cells are mediated via apoptosis induction, G2/M phase cell cycle arrest, cell migration and invasion inhibition and targeting of mTOR/PI3K/AKT signalling pathway.